Chiseling away at a concrete legacy: Engaging with Communist-era heritage and memory in Albania. (August 2014) - Eaton, Jonathan; Roshi, Elenita
Abstract : Albania spent much of the 20th century under one of Europe's most ideologically repressive regimes. In order to justify and ostensibly protect this system, the Albanian Communist regime (1944–1992) constructed a massive array of defensive works, which formed a major piece of the Hoxhaist (after Enver Hoxha) aesthetic. Twenty years after the fall of Communism, Albanians have gained the freedom to travel abroad, but have largely avoided addressing the legacy of this difficult past within their own society. Based on the theory that some aspects of traumatic memory can be addressed through confronting and re-signifying material heritage, we explore some localized cases in order to comprehend the roots of this concrete legacy, combining theoretical analysis with field experiences in collaboration with the Gjirokastra Foundation. We suggest one possible approach to the difficult process of creating open community dialogue to deal with the scars of a traumatic past and thus begin the healing process.